In vitro micronucleus assay: Method for assessment of nanomaterials using cytochalasin B - Farabaugh, Christopher S.; Doak, Shareen; Roy, Shambhu; Elespuru, Rosalie (Frontiers in Toxicology, 2023)
The in vitro micronucleus (MNvit) assay is used to evaluate the aneugenic and clastogenic potential of a test material based upon its ability to induce micronuclei in the cells. This protocol is provided for testing of nanomaterials (NM) with standard cell lines in the absence of metabolic activation. The use of cytochalasin B (CytoB) and the analysis of binucleated cells in the cytokinesis-block version of the micronucleus assay ensures that cells analyzed have undergone cell division, which is required for expression of DNA damage and micronucleus formation. Issues specific to NM that were problematic with standard test methods are addressed, including test system choice, dose selection, test material exposures, CytoB timing, cytotoxicity determination, and DNA damage expression time. A step-by-step protocol for in vitro micronucleus assessment of NM is provided.